Quality of electronic treatment records and adherence to prophylaxis in haemophilia and von Willebrand disease: Systematic assessments from an electronic diary. Issue 6 (21st October 2020) - Tiede, Andreas; Bonanad, Santiago; Santamaria, Amparo; Goldmann, Georg; Canaro, Mariana; Palomero, Antonio; Frade, Luis J. G.; Eduardo Megias‐Vericat, Juan; Martinez, Fernanda; Garcia Candel, Faustino; Jimenez Yuste, Victor; Sparber‐Sauer, Monika; et al.
Abstract: Introduction: Haemoassist TM 2 is an electronic system designed for people with bleeding disorders and their physicians to record prophylactic infusions and treatment of bleeds. It aims to improve adherence by permitting reminders and accuracy of documentation by facilitating real‐time reporting. Aim: To assess documentation quality and adherence to prophylactic regimens in patients with haemophilia A, haemophilia B or von Willebrand disease who are using Haemoassist TM 2. Methods: Ten centres enrolled consecutive patients, who had been using Haemoassist TM 2 for ≥ 3 months (Cohort 1, 'quality of documentation'). Of these, patients who had a specified prophylactic regimen in Haemoassist TM 2 for ≥ 3 months were eligible for inclusion in Cohort 2 ('adherence to prophylaxis'). Results: Cohort 1 comprised 796 patients (71% with severe haemophilia A; median 20.5 months of Haemoassist TM 2 use). The most common method of documentation for patients was using the mobile app; the median time between infusion and documentation was 4 hours using the app, compared with 85 hours using a web portal on a stationery device. The median total annualised number of infusions was consistent in the first and last 3 months of documentation (128; IQR: 70‐184 and 120; IQR 64‐176, respectively). Cohort 2 comprised 202 patients (79% severe haemophilia A; median of 13 months on prophylactic regimen in Haemoassist TM 2). The rate of adherence to prophylaxis was 83%; median deviation between planned and actual infusion time was ± 2 hours. Conclusion: Haemoassist TM 2 was used consistently over prolonged periods of time and allowed for precise analysis of adherence to prophylaxis.